Does It Matter What I Say? Using Language to Examine Reactions to Ostracism as It Occurs - Klauke, Fabian; Kauffeld, Simone (Frontiers in Psychology, 2020)
Most of our knowledge about how social exclusion affects those who ostracize and those who are being ostracized is based on questionnaires administered after the ostracism situation is over. In this research, we strive to further our understanding of the internal dynamics of an ostracism situation. We therefore examine individuals’ language—more specifically, function words—as a behavior indicative of psychological processes and emergent states that can be unobtrusively recorded right in the situation. In online chats, 128 participants talked about a personal topic in groups of three. In the experimental group (n = 79), two conversation partners ignored every contribution by the third. We found that, compared to the control group, these targets of ostracism used language indicative of a self-focus and worsened mood, but not of social focus or positivity, although positivity was related to a writer’s likeability. Sources of ostracism use language suggesting that they are distancing themselves from the situation, and they further engaged in victim derogation. We discuss how our results highlight the severity and potential self-sustainability of ostracism.